EFEKTIVITAS PELAYANAN PERIZINAN PADA BADAN PENANAMAN MODAL DAN PERIZINAN TERPADU (BPMPT) KOTA SURAKARTA - Wahyu Bhudianto, Miftachul Fauzan, Damayanti Suhita & (Transformasi, 2015)
This study is a describtive qualitative tried to describe effectiveness permit service on BPMPT city of Surakarta. Data collecting with observation technique, interview, and documentation study. Election informan with purposive sampling. While to analysis researcher data by using technique interactive analysis. The result showed that effectiveness permit service BPMPT city of Surakarta have earned to implementation as according service standard based and mission of BPMPT city of Surakarta. According to service implementation with service standard which have been executed by BPMPT city of Surakarta can effectively suported by service officer claimed to can serve customer batter.Key word: effectiveness, permit service